The effect of exercises by using auxiliary means to developing the explosive power and defensive follow-up for young basketball players - Ishhab Abdul Hussein, Ali; Hussein Abdul Ameer, Nassr (International Journal of Psychosocial Rehabilitation, 2020)
The importance of research by use of exercises with auxiliary means and with modern sports equipment is because it has a great role to play in the development of the basketball game, which may be more effective and safe for players, especially after it has been developed in an accurate and standardized scientific manner and with suitable resistances for the sample. As for the research problem, it is represented by the apparent decline in the explosive power and the defensive follow-up for young basketball players. The thesis also aimed to: Identify the effect of exercises using an auxiliary means to developing the explosive power and defensive follow-up for young basketball players; the researchers also hypothesized that exercises by using an auxiliary means effect develop explosive power and defensive follow-up for young basketball players.In the third part, the researchers used the experimental method on a sample of (12) players for the AlHillah youth club with basketball, as the experimental group used the exercises prepared by the researchers on the aid for a period of (8 weeks) at (3) units per week, the researchers conducted the pre- tests before implementing the exercises by an auxiliary means as part of the experimental curriculum steps, after the physical and movement abilities were identified and tested, and individual and group skills were determined to initiate the attack and measured through visualization and evaluation by the arbitrators, and the tests were repeated after the completion of the exercises with an auxiliary means within steps. The experimental method and the results were treated statistically by using SPSS ) to extract the results. Consequently, the results were presented and discussed in chapter four. The exercises using the aid have a clear effect on the development of the explosive ability of the players in the experimental group, as well as the use of exercises using the assistive device having a great role in developing the defensive follow-up of the players in the experimental group, as well as the use of auxiliary means with rubber ropes that saved effort and time for the coach and the player in developing explosive ability and defensive follow-up well; it is suitable for young people. The researchers also recommended By using an auxiliary means, which contains a variety of rubber ropes, in developing some of the physical and motor abilities for basketball players.